Steroid dependency and trends in prescribing for inflammatory bowel disease – a 20‐year national population‐based study. Issue 5 (4th July 2016) - Chhaya, V.; Saxena, S.; Cecil, E.; Subramanian, V.; Curcin, V.; Majeed, A.; Pollok, R. C.
Summary: Background: It is unclear whether adherence to prescribing standards has been achieved in inflammatory bowel disease (IBD). Aim: To determine how prescribing of 5‐aminosalicylates (5‐ASAs), steroids and thiopurines has changed in response to emerging evidence. Methods: We examined trends in oral and topical therapies in 23 509 incident IBD cases (6997 with Crohn's disease and 16 512 with ulcerative colitis) using a nationally representative sample between 1990 and 2010. We created five eras according to the year of diagnosis: era 1 (1990–1993), era 2 (1994–1997), era 3 (1998–2001), era 4 (2002–2005) and era 5 (2006–2010). We calculated the proportion of patients treated with prolonged 5‐ASAs (>12 months) and steroid dependency, defined as prolonged steroids (>3 months) or recurrent (restarting within 3 months) steroid exposure. We calculated the cumulative probability of receiving each medication using survival analysis. Results: Half of the Crohn's disease patients were prescribed prolonged oral 5‐ASAs during the study, although this decreased between era 3 and 5 from 61.8% to 56.4% ( P = 0.002). Thiopurine use increased from 14.0% to 47.1% ( P < 0.001) between era 1 and 5. This coincided with a decrease in steroid dependency from 36.5% to 26.8% ( P < 0.001) between era 1 and 2 and era 4 and 5 respectively. In ulcerative colitis, 49% of patients were maintained on prolonged oral 5‐ASAs. Despite increasing thiopurine use, repeated steroid exposure increased from 15.3% to 17.8% ( P = 0.02) between era 1 and 2 and era 4 and 5 respectively. Conclusions: Prescribing in clinical practice insufficiently mirrors the evidence base. Physicians should direct management towards reducing steroid dependency and optimising 5‐ASA use in patients with IBD.